Modeling of development trajectories in the multidimensional space: socio-geographic interpretation - Niemets, Kostyantyn; Sehida, Kateryna; Niemets, Lyudmyla; Telebienіeva, Ievgeniia; Kravchenko, Kateryna (Human Geography Journal, 2018)
The purpose of this paper is justification of methodological peculiarities of the development trajectories modeling in the multidimensional space from the positions of social geography; their practical application (geodemographic process in Kharkiv region is taken as an example). The object of social geography is social and geographical system and social and geographical process. Combination of natural, social and economic systems in it creates a unique variety of features and properties requiring consideration of a large number of these systems parameters. According to the geographical, system and synergetic approach all these processes are described in hundreds of parameters. Adequate and correct mathematical processing of such actual material is possible only with use of virtual multidimensional geographic space where the mathematical model of the real development trajectory of the object or process is offered. The main estimation parameters are given, in particular the main diagonal in the hypercube of the multidimensional space is considered as the standard of optimal development. Comparison of the real trajectory with the optimal, determining the projection of the vector of development on the optimal trajectory, deviations from the optimal trajectory contain information on the peculiarities of the process.The proposed method was used for modeling of the geodemographic development trajectory in districts of Kharkiv region for 2002-2015 on the basis of 72 initial statistical parameters which are characterizing this process to demonstrate its peculiarities on the results of certain studies. The grouping of the districts of Kharkiv region, temporal peculiarities are shown, the phases of progressive and regressive demographic development for the studied period are established taking into account a considerable amount of the initial data. Modeling the development path allows us to define a clear perspective, to model and predict further development, to plan the pace of development. It is also a convenient monitoring tool; it also helps to develop scientifically-based management measures, etc.